PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA ALPHA HOTEL PEKANBARU - ", Destriana; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine how much influence the job training and career development on employee performance at the Pekanbaru Alpha Hotel. The sample in this study was taken as many as 66 respondents and the technique used was Total Sampling. The data in this study used a survey method through a questionnaire filled out by employees. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that job training has a positive effect on employee performance. Career development has a positive effect on employee performance. And simultaneously job training and career development have a positive effect on employee performance. Future studies are suggested to use other methods in examining job satisfaction, for example through in-depth interviews with respondentsÂ Keywords: Job Training, Career Development, and Employee Performance